Interferon-Lambda 1 Inhibits Staphylococcus aureus Colonization in Human Primary Keratinocytes - Wu, Xia; Zhao, Yan; Gu, Ying; Li, Kun; Wang, Xiaojie; Zhang, Jianzhong (Frontiers in Pharmacology, 2021)
Atopic dermatitis (AD) is a common inflammatory skin disease. Staphylococcus aureus (S. aureus) colonization in skin lesions occurs in approximately 70% of AD patients. It has been found that IFN-λ1 can inhibit the colonization of S. aureus in normal human nasal mucosa. IFN-λ1 can increase IL-28RA in infected human keratinocytes. In this study, we found that IFN-λ1 can increase mRNA expression of FLG and antimicrobial peptides (AMPs), and inhibit TSLP mRNA expressioni in infected human keratinocytes. IFN-λ1 can increase intracellular ROS level, decrease STAT1 phosphorylation and inhibit the colonization of S. aureus in human primary keratinocytes. These effects were attenuated by knocking-down IL-28R and NADPH oxidase inhibitor, suggesting that this function was mediated by JAK-STAT1 signaling pathway. These results suggesti that IFN-λ1 might have an inhibitory effect on S. aureus colonization in AD lesions. Our foundings might have potential value in the treatment for AD.